The Role of Cognitive Reserve in Post-Stroke Rehabilitation Outcomes: A Systematic Review - Debora Bertoni; Stefania Bruni; Donatella Saviola; Antonio De Tanti; Cosimo Costantino (Brain Sciences)
Background/Objectives: Stroke remains a major cause of disability and death, with survivors facing significant physical, cognitive, and emotional challenges. Rehabilitation is crucial for recovery, but outcomes can vary widely. Cognitive reserve (CR) has emerged as a factor influencing these outcomes. This systematic review evaluates the role of CR in post-stroke rehabilitation, examining whether higher CR is associated with better outcomes. Methods: A systematic search of PubMed, Google Scholar, Scopus, and Cochrane Library databases was conducted for studies published between 2004 and 2024. Studies examining social-behavior CR proxies (e.g., education, bilingualism) and their impact on post-stroke outcomes were included. Data were analyzed using descriptive statistics. The study quality was assessed using the Methodological Index for NOn-Randomized Studies (MINORS) scale. Results: Among 3851 articles screened, 27 met the inclusion criteria. Higher education levels, bilingualism, and engagement in cognitively stimulating activities were associated with better cognitive outcomes and functional recovery. Lower socioeconomic status (SES) correlated with poorer outcomes. Early rehabilitation and dynamic CR proxies showed stronger associations with cognitive recovery than static ones. Conclusions: CR may predict post-stroke rehabilitation outcomes, with education, bilingualism, and active engagement in cognitive activities showing potential benefits. Future research should explore CR’s role alongside factors like lesion location and severity in enhancing recovery.